A randomised placebo-controlled double-blind multicentre trial comparing antibiotic therapy with placebo in the treatment of uncomplicated acute appendicitis: APPAC III trial study protocol - Sippola S; Grönroos J; Sallinen V; Rautio T; Nordström P; Rantanen T; Hurme S; Leppäniemi A; Meriläinen S; Laukkarinen J; Savolainen H; Virtanen J; et al. (My University, 2022)
Introduction Recent studies show that antibiotic therapy is safe and feasible for CT-confirmed uncomplicated acute appendicitis. Spontaneous resolution of acute appendicitis has already been observed over a hundred years ago. In CT-confirmed uncomplicated acute diverticulitis (left-sided appendicitis), studies have shown no benefit from antibiotics compared with symptomatic treatment, but this shift from antibiotics to symptomatic treatment has not yet been widely implemented in clinical practice. Recently, symptomatic treatment of uncomplicated acute appendicitis has been demonstrated in a Korean open-label study. However, a double-blinded placebo-controlled study to illustrate the role of antibiotics and spontaneous resolution of uncomplicated acute appendicitis is still lacking.
Methods and analysis The APPAC III (APPendicitis ACuta III) trial is a multicentre, double-blind, placebo-controlled, superiority randomised study comparing antibiotic therapy with placebo in the treatment CT scan-confirmed uncomplicated acute appendicitis aiming to evaluate the role of antibiotics in the resolution of uncomplicated acute appendicitis. Adult patients (18–60 years) with CT scan-confirmed uncomplicated acute appendicitis (the absence of appendicolith, abscess, perforation and tumour) will be enrolled in five Finnish university hospitals.
Primary endpoint is success of the randomised treatment, defined as resolution of acute appendicitis resulting in discharge from the hospital without surgical intervention within 10 days after initiating randomised treatment (treatment efficacy). Secondary endpoints include postintervention complications, recurrent symptoms after treatment up to 1 year, late recurrence of acute appendicitis after 1 year, duration of hospital stay, sick leave, treatment costs and quality of life. A decrease of 15 percentage points in success rate is considered clinically important difference. The superiority of antibiotic treatment compared with placebo will be analysed using Fisher’s one-sided test and CI will be calculated for proportion difference.
Ethics and dissemination This protocol has been approved by the Ethics Committee of Turku University Hospital and the Finnish Medicines Agency (FIMEA). The findings will be disseminated in peer-reviewed academic journals.